CK-MM Polymorphism is Associated With Physical Fitness Test Scores in Military Recruits. Issue 9 (1st September 2015) - Sprouse, Courtney; Tosi, Laura L.; Gordish-Dressman, Heather; Abdel-Ghani, Mai S.; Panchapakesan, Karuna; Niederberger, Brenda; Devaney, Joseph M.; Kelly, Karen R.
ABSTRACT: Objective: Muscle-specific creatine kinase is thought to play an integral role in maintaining energy homeostasis by providing a supply of creatine phosphate. The genetic variant, rs8111989, contributes to individual differences in physical performance, and thus the purpose of this study was to determine if rs8111989 variant is predictive of Physical Fitness Test (PFT) scores in male, military infantry recruits. Methods: DNA was extracted from whole blood, and genotyping was performed in 176 Marines. Relationships between PFT measures (run, sit-ups, and pull-ups) and genotype were determined. Results: Participants with 2 copies of the T allele for rs8111989 variant had higher PFT scores for run time, pull-ups, and total PFT score. Specifically, participants with 2 copies of the TT allele (variant) ( n = 97) demonstrated an overall higher total PFT score as compared with those with one copy of the C allele ( n = 79) (TT: 250 ± 31 vs. CC/CT: 238 ± 31; p = 0.02), run score (TT: 82 ± 10 vs. CC/CT: 78 ± 11; p = 0.04) and pull-up score (TT: 78 ± 11 vs. CC/CT: 65 ± 21; p = 0.04) or those with the CC/CT genotype. Conclusion: These results demonstrate an association between physical performance measures and genetic variation in the muscle-specific creatine kinase gene (rs8111989).